Blood lipid profile study in patients with acute stroke - AL-Bayatti, Ansam A.; Gadeer, widadk A.; Mahmoud, Hayder N. (Journal of the Faculty of Medicine Baghdad, 2005)
Background: The accumulation of the lipid in the vascular smooth muscle cell within the arterial intima is a key process of the pathogenesis of atherosclerosis. Atherosclerosis is a degenerative disease of blood vessels leading to stroke. Materials & Methods.One hundred and ten patients with acute stroke were included in this study 88 patients with ischaemic or infarction stroke and 22 patients with hemorrhagic type ) as well as thirty apparently normal healthy subjects as controls. Results.Triglycerides levels and AI only were statistically significant in ischaemic type of stroke (P<0.005) while other lipid fractions were similar to the control values. Conclusion: Acute stroke patients (infarction type) had significantly elevated TG and low Al. While those with hemorrhagic type had more or less similar lipid profile to normal control. In general the higher the TG level the poorer the outcome in patients with acute stroke.